Power control techniques for fuel cell hybrid electric vehicles: A comparative study. (January 2022) - Sid, Mohamed Nacereddine; Becherif, Mohamed; Aboubou, Abdenacer; Benmouna, Amel
Highlights: State-of-art review of fuel cell hybrid vehicles technology. Overview of the architecture of the hybrid system and its energy sources models. Review of real-time proton exchange membrane fuel cell emulator verified by experimental results. Discussion and comparison of different online energy management strategies studied. The proposed energy management strategy is able to be one of the most promising online techniques. Abstract: This paper provides a comparative analysis of the techniques of energy management strategy for a fuel cell hybrid electric vehicle. A Proton Exchange Membrane Fuel Cell device and Lithium-ion batteries are included within the multi-source. Therefore, a comparative analysis has been carried out to follow a successful approach in the hybrid system in terms of hydrogen usage in the Fuel Cell and regulating the Lithium-Ion batteries state of the charge. The various methods have been simulated by using Advanced Vehicle Simulator in MATLAB/Simulink. These simulations have been carried out with five standard driving cycles in which the energy management strategy understudy has been tested and compared. Due to the successful use of sources, the simulation results indicate the proposed technique's superiority and economic success (5 to 15% decrease in fuel consumption). Experimental tests have also been performed to verify the findings of the simulation using a fuel cell emulator. Graphical abstract: Image, graphical abstract